Continuous Movement Mechanism of Oil Droplets Adhered on Surfaces with Different Wettability in the Flow Field - Han, Yunrui (Langmuir : the ACS journal of surfaces and colloids, 2020)
In this aticle, the continuous movement patterns and characteristic parameters of oil droplets on surfaces with different wettability immersed in a laminar flow field were observed, and the change rules of the geometric parameters of oil droplets under different experimental conditions were obtained. Then, the factors influencing the continuous moving behaviors of the oil droplets were analyzed, and the continuous movement velocity of the oil droplets under different experimental conditions was demonstrated. On this basis, the change law of the continuous movement velocity of oil droplets with the flow velocity was discussed. In addition, the coupling effect of the oil drops' height, surface properties, and water flow velocity on the continuous movement of oil droplets was studied, and the critical conditions for the continuous movement were obtained. According to the critical conditions, the mathematical model which described the law of continuous motion of the oil droplets adhered on surfaces with different wettability in the laminar flow field was established. The quantitative relationships among the average continuous moving velocity of oil droplets, physical properties, geometric parameters, water flow velocity, and surface wettability were obtained, which defined the necessary conditions for the uniform and accelerated movement of oil droplets, providing an important basis for choices of suitable surface wettability and flow field conditions in practical engineering applications